The Effect of Corporate Social Responsibility (CSR) and Financial Ratio to Corporate Values - Tanto Kurnia; Mathius Tandiontong (The Indonesian Journal of Accounting Research, 2015)
Abstract: This paper studies the effect of corporate activities in environmental and social responsibility (CSR), as well as financial ratios, on corporate values. Corporate managers may only be focusing on pleasing their investors and forget about their responsibilities to the other stakeholders. The performance of corporate financial ratios portrays manager’s responsibilities toward shareholders and investors, while CSRs incorporate the whole stakeholders. Corporate managers, who are responsible for corporate sustainability, would focus not only on the interest of shareholders, instead, to the overall stakeholders to reduce the agency problem. We examine public companies which are listed on the Indonesia Stock Exchange, focusing in the period from 2006 to 2013. A combination between time series and cross-section data make the sample data of this study fits into the category of panel data. Some statistical tests are performed to get an overview of the relationship between CSR and financial ratios to corporate values, which is quantified through Market Value Added (MVA) analysis. Corporate activities in environmental and social responsibilities are measured by certifications owned by the corporation, such as ISO9000, ISO14000, OHSAS18000 and the availability of employee stock ownership plan (ESOP). On the other hand, financial performances are measured through financial ratios, including current ratio, debt-to-equity ratio, total asset turnover, return on sales and price-earnings ratio.Abstract: Makalah ini mempelajari pengaruh kegiatan perusahaan dalam tanggung jawab sosial dan lingkungan (CSR), serta rasio keuangan, pada nilai-nilai perusahaan. Manajer perusahaan mungkin hanya berfokus pada menyenangkan investor mereka dan melupakan tanggung jawab mereka kepada para pemangku kepentingan lainnya. Kinerja rasio keuangan perusahaan menggambarkan tanggung jawab manajer terhadap pemegang saham dan investor, sementara CSR melibatkan seluruh pemangku kepentingan. Manajer perusahaan, yang bertanggung jawab untuk keberlanjutan perusahaan, akan fokus tidak hanya pada kepentingan pemegang saham, sebaliknya, kepada seluruh pemangku kepentingan untuk mengurangi masalah keagenan. Kami memeriksa perusahaan publik yang terdaftar di Bursa Efek Indonesia, berfokus pada periode 2006-2013. Kombinasi antara seri waktu dan data penampang membuat data sampel dari penelitian ini sesuai dengan kategori data panel. Beberapa tes statistik dilakukan untuk mendapatkan gambaran tentang hubungan antara CSR dan rasio keuangan dengan nilai-nilai perusahaan, yang dikuantifikasi melalui analisis Nilai Tambah Pasar (MVA). Kegiatan perusahaan dalam tanggung jawab lingkungan dan sosial diukur dengan sertifikasi yang dimiliki oleh perusahaan, seperti ISO9000, ISO14000, OHSAS18000 dan ketersediaan rencana kepemilikan saham karyawan (ESOP). Di sisi lain, kinerja keuangan diukur melalui rasio keuangan, termasuk rasio lancar, rasio utang terhadap ekuitas, total perputaran aset, laba atas penjualan dan rasio harga-laba.